Back Cover: Coherent Ising Machines with Optical Error Correction Circuits (Adv. Quantum Technol. 11/2021). Issue 11 (8th November 2021) - Reifenstein, Sam; Kako, Satoshi; Khoyratee, Farad; Leleu, Timothée; Yamamoto, Yoshihisa
Abstract : The graph on the cover shows the evolution of average energies of many trajectories in a coherent Ising machine (CIM). In some cases, the final state of CIM reaches a ground state (solution), while in some other cases the CIM states are trapped in the first, second and third excited states (non‐solution). The CIM is a noise‐driven stochastic computing machine and this image shows such a random character. For further information see article number 2100077 by Yoshihisa Yamamoto and co‐workers.